The impact of financial incentives on SNAP transactions at mobile produce markets. - Rummo, Pasquale E.; Lyerly, Reece.; Rose, Jennifer.; Malyuta, Yelena.; Cohen, Eliza Dexter.; Nunn, Amy. (Tufts University. Tisch Library., 2021)
Keywords: Mobile produce markets, Financial incentives, Fruit and vegetable purchases.; Springer Open.